Pengembangan Media Pembelajaran Interaktif Game PowerPoint Materi Siklus Makhluk Hidup Pada Siswa Kelas IV Sekolah Dasar - Amirotush Sholihah; Akhmad Fauzi; Yhasinta Agustyarini (Program Studi PGMI STAI Daruttaqwa Gresik, 2022)
Technological developments also have an impact on the world of education. Teachers to be able to use technology to create learning that is fun, interactive and motivating. One of them is using a computer program, namely making interactive learning media for PowerPoint games. The purpose of this study is to determine the response of teachers and students as well as the effectiveness of interactive learning media PowerPoint game material cycle of living things in fourth grade students of SDI Asy-Syarif. This study uses Research and Development research using the ADDIE model, namely through the stages of analysis, design, development, implementation, and evaluation as research steps. Data collection is done by observation, interviews, expert validation, and questionnaires. The data analysis techniques used were validation sheet analysis, questionnaire analysis, and quantitative data analysis. The results of this study indicate how accurate material experts are 92%, media experts are 86%, and linguists are 97.7%. The validation results indicate that the PowerPoint game interactive learning media is very feasible to use. The results of student responses get a prize of 95.2% with a very good category while the results of the teacher's response get a prize of 82.5% with a good category to use. The quantitative data analysis shows an average of 60.60%. So it can be said that the PowerPoint interactive game learning media developed is very feasible, good for use and quite effective for improving student learning outcomes.